Nutrition-sensitive landscapes: approach and methods to assess food availability and diversification of diets - Kennedy, G.; Raneri, Jessica Evelyn; Termote, Céline; Nowak, V.; Remans, R.; Groot, Jeroen C.J.; Thilsted, Shakuntala H. (Routledge, 2017)
Sustainable intensification has recently been developed and adopted as a key concept and driver for research and policy in sustainable agriculture. It includes ecological, economic and social dimensions, where food and nutrition security, gender and equity are crucial components. This book describes different aspects of systems research in agriculture in its broadest sense, where the focus is moved from farming systems to livelihoods systems.